Novel IL2RG Gene Mutation in One of Dizygotic Twins Causing Profound Changes of Receptor Structure - Rutkowska-Zapała, Magdalena; Szaflarska, Anna; Kluczewska, Anna; Ciȩciwa, Julia; Plewka, Jacek; Michalska, Anna; Siedlar, Maciej (Frontiers in Pediatrics, 2022)
In this study, we report a 4-month-old boy with T−B+NK− severe combined immunodeficiency (SCID) due to a novel mutation in exon 2 of IL2RG, the gene encoding the interleukin (IL) common gamma chain (γc) of the cytokine receptors for IL-2, IL-4, IL-7, IL-9, IL-15, and IL-21. The patient was born from a twin pregnancy. He manifested recurrent infections of the gastrointestinal tract, whereas his twin brother was asymptomatic with no immune defects. In order to evaluate the effect of this unreported variant on the protein structure, a structural modeling process was performed showing prominent biochemical alterations of the protein features, including molecular weight, isoelectric charge, and possible changes to its secondary and tertiary structure.